Construction of plug-and-play local protection system for smart substation. Issue 1 (February 2021) - Chao, Wujie; Tang, Zhijun; Lin, Guodong; Hu, Wenwang; Zhuang, Li; Xu, Jie
Abstract: This paper studies the application of plug-and-play location-based protection device in smart substation, introduces the hardware and software design scheme of smart substation plug-and-play location-based protection device, in order to improve the environmental adaptability and operation reliability of smart substation protection device, and reduce the operation cost of substation. In order to improve the protection performance and operation reliability of smart substation, the practicability and effectiveness of plug and play local-based protection device and intelligent management unit software are verified.